Encountering the medieval in modern Jewish thought - Diamond, James Arthur.; Hughes, Aaron W., 1968- (Supplements to The Journal of Jewish Thought and Philosophy, 2012)
The term "medieval" performs a great deal more intellectual work in modern Jewish Thought than simply acting as a referent to a particular historical era. During the nineteenth century, often for Jews who were increasingly alienated from their own tradition, the "medieval" functioned primarily as a bearer of identity in a rapidly changing and secular world. Each chapter in Encountering the Medieval in Modern Jewish Thought addresses a different return to the medieval, ranging from the Enlightenment to the contemporary period, that clothed itself in the language of renewal and of retrieval. The volume engages the full complexity and range of meaning the term "medieval" carries for modern Jewish Thought.